Beryllium levels in the mangrove snail, Nerita lineata and surface sediments from Peninsular Malaysian mangrove area - Chee, Kong Yap; Wan, Hee Cheng (Universiti Kebangsaan Malaysia, 2015)
The beryllium (Be) concentrations were determined in the shells, opercula and soft tissues of the Nerita lineata and in the surface sediments collected from nine geographical sites of Peninsular Malaysian mangrove area in April 2011. The ranges of Be concentrations (μg/kg dry weight) were: <1.00- 4.00 for shells, <1.00-2.00 for opercula and 3.00-41.00 for soft tissues of N. lineata. For sediments, Be ranges were found between 1200 and 3810 μg/kg dry weight. The distribution of Be was found to be: sediment> soft tissues > shells ≥ opercula. The insignificant (p>0.05) relationships of Be between snails and sediments and low bioaccumulation factor (ratio of soft tissues to sediment) (<1.00), could be attributed to the fact that Be contamination being not serious in the Peninsular Malaysian mangrove area. The snail N. lineata as a good biomonitor of Be needs further investigations. Lastly, Peninsular Malaysia mangrove was not contaminated by Be based on the present findings.